Pemanfaatan Aplikasi Google Slides Berbasis Project Based Learning dalam Pembelajaran Sejarah - Iis Husnul Hotimah (Departement of Mathematics Education, 2023)
Using Google Slides is a simple yet versatile way to teach remotely. Google automatically saves each slide, the toolbar is easy to use, and slides can be shared (and saved) by students. Giving students access to slides by sharing the editor or teacher version link is a necessary first step towards collaborative virtual learning through Google Slides. This paper provides a comprehensive explanation of the use of Project-based Google Slides in combination with other applications such as Google Jamboard to create an innovative and fun virtual learning environment. This research uses a descriptive qualitative method where researchers will explain in detail how history teachers can give project assignments to students through the Google Slides application. Data collection is done by collecting reference sources and then the data is described in detail